(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This article scientifically analyzes the formation, historical development and stages of artistic crafts in the Kashkadarya region. It separately considers the main types of crafts - jewelry, embroidery and metalworking, highlighting their specific features, technological processes and the symbolic meaning of patterns and ornaments. It also studies the impact of socio-political changes in the 20th century on traditional art, the threat of extinction of crafts and the processes of their revival in modern times. The study substantiates the role of artistic crafts in society as a centuries-old cultural heritage of the Kashkadarya region, as well as its spiritual and practical significance